Entre Lázaro Cárdenas y el Che Guevara: las izquierdas mexicanas en los años sesenta - Servín, Elisa (El Colegio de México, A.C., 2024)
This article addresses the debates within the Mexican left following the defeat of the railroad workers’ movement and the victory of the Cuban Revolution in 1959. Its central hypothesis is that the National Liberation Movement (MLN), led by former president Lázaro Cárdenas, functioned as a transitional space from an old left downstream from revolutionary nationalism and a new left that promoted a political project which sought to transcend these ideological frameworks. Although the MLN had an ephemeral existence in the sixties, many of its militants led peasant mobilizations, student protests, cultural publications and Guevarist guerrilla focos throughout the decade. According to the author, the Mexican left underwent a generational renewal, in which young people, students and intellectuals took center stage as potential revolutionary subjects.